THE ROLE OF SOCIAL MEDIA IN THE ERA OF DIGITAL TRANSFORMATION AS A MEANS OF COMMUNICATION KARANG TARUNA COMMUNITY KAMPUNG PARUNG SERAB CILEDUG - Yunus Yunus; Slamet Raharjo; Murni Handayani; Natasya Arifah; Rafli Rafli; Nuraini Sitepu; Allam Ramzy; Widuri Indana Saleha (International Journal of Engagement and Empowerment, 2021)
Social media is where the communication tool is by the user in the social process. At the same time, digital transformation uses technology to transform analog processes into digital. We have digitalization in all areas of our lives, from smartwatches to artificial intelligence-enabled household assistants. The role of social media in the era of transformation in the village serab ciledug is still not maximal in social media use, therefore Kewan then the community conducted in the organization of taruna taruna kampung parung serab is to provide education or direction in social media in the current digital transformation era. So that when the organization of taruna taruna kampung parung serab ciledug in the direction of activities in the organization area, can return information which of the community perseverance activities (PKM) this. So by means of the way then the activities of salting this community can stretch the coral taruna kampung parung serab ciledug to be able to increase efficiency and efficiency in social media. So that by also can be dikung far coral activities taruna kampung parung serab ciledug